eComplexity: validation of a complex thinking instrument from a structural equation model - Vázquez-Parra, José Carlos; Henao-Rodriguez, Linda Carolina; Lis-Gutiérrez, Jenny Paola; Castillo-Martínez, Isolda Margarita; Suarez-Brito, Paloma (Frontiers in Education, 2024)
The eComplexity instrument aims to measure the perception of achievement in the complex thinking competency and its sub-competencies. To ensure the reliability of this instrument, validation processes like the one presented in this article are necessary. Methodologically, this study evaluates data from 1,037 university students in Mexico, confirming the statistical validity and reliability of the instrument. As a result, the demonstrated reliability of the eComplexity instrument as a tool for measuring perceived achievements in complex thinking provides a valuable resource for assessing the effectiveness of educational interventions. Consequently, this research contributes to a more informed approach to fostering critical thinking skills, benefiting both theoretical exploration and practical application in educational settings. The study employs the Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate students’ self-perceptions of their performance in complex thinking and its sub-competencies, thus advancing the field of educational measurement. Academically, it enriches the discourse on the design and validation of instruments, offering a rigorous model for future efforts in measuring cognitive competencies. Practically, the study’s results inform educational practice by identifying systemic and scientific thinking as key to developing complex thinking skills. This knowledge enables educators to more effectively adapt teaching strategies and curricular designs, aiming to enhance students’ ability to navigate the complexities of the modern world.